2022
DOI: 10.1093/nar/gkac826
|View full text |Cite
|
Sign up to set email alerts
|

The TRIPLE PHD FINGERS proteins are required for SWI/SNF complex-mediated +1 nucleosome positioning and transcription start site determination in Arabidopsis

Abstract: Eukaryotes have evolved multiple ATP-dependent chromatin remodelers to shape the nucleosome landscape. We recently uncovered an evolutionarily conserved SWItch/Sucrose Non-Fermentable (SWI/SNF) chromatin remodeler complex in plants reminiscent of the mammalian BAF subclass, which specifically incorporates the MINUSCULE (MINU) catalytic subunits and the TRIPLE PHD FINGERS (TPF) signature subunits. Here we report experimental evidence that establishes the functional relevance of TPF proteins for the complex acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 100 publications
2
23
0
Order By: Relevance
“…In contrast, the SYD-containing complexes selectively contain paralog SWI3D but not SWI3A/B/C, and include a complex-specific subunit, encoded by S YD sub- S WI/SNF Interacting P rotein 1/2/3 ( SSIP1 , SSIP2, or SSIP3 ). Finally, consistent with the recent report (Diego-Martin et al, 2022), the MINU- containing complexes do not contain the GIF2 subunit (SS18 paralogs) found in both BRM- and SYD-containing complexes, incorporate selective paralogs (that is, SWI3A/B but not SWI3C and SWI3D) and include a number of complex-specific subunits, including BSH, BRD5, SHH2, TPF1/2, OPF1/2, PSA1, and PSA2.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…In contrast, the SYD-containing complexes selectively contain paralog SWI3D but not SWI3A/B/C, and include a complex-specific subunit, encoded by S YD sub- S WI/SNF Interacting P rotein 1/2/3 ( SSIP1 , SSIP2, or SSIP3 ). Finally, consistent with the recent report (Diego-Martin et al, 2022), the MINU- containing complexes do not contain the GIF2 subunit (SS18 paralogs) found in both BRM- and SYD-containing complexes, incorporate selective paralogs (that is, SWI3A/B but not SWI3C and SWI3D) and include a number of complex-specific subunits, including BSH, BRD5, SHH2, TPF1/2, OPF1/2, PSA1, and PSA2.…”
Section: Resultssupporting
confidence: 91%
“…For example, for SAS complexes, the three SSIPs (SSIP1, SSIP2, SSIP3) are separately incorporated into the SAS complexes (Figure 1B). Similarly, OPF1, the MAS-specific subunit, did not exist in the OPF2-containing MAS complexes (Diego-Martin et al, 2022). Finally, BAS- specific subunit BRIP1 cannot co-immunoprecipitated with BRIP2, and BRD1 cannot co-immunoprecipitated with BRD2 and BRD13 (Figure 1B).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the model plant Arabidopsis ( Arabidopsis thaliana ), the SWI/SNF CRC is a multi-subunit machine containing four core catalytic ATPases [BRAHMA (BRM), SPLAYED (SYD), Chromatin Remodeling Factor 12/MINUSCULE 1 (CHR12/MINU1), and CHR23/MINU2] ( Wagner and Meyerowitz, 2002 ; Farrona et al., 2004 ; Bezhani et al., 2007 ; Sang et al., 2012 ), a single SNF5 subunit called BUSHY (BSH) ( Brzeski et al., 1999 ), four SWI3 proteins (SWI3A, SWI3B, SWI3C, and SWI3D) ( Sarnowski et al., 2005 ), two SWI/SNF ASSOCIATED PROTEINS 73 (SWP73A and SWP73B) ( Jégu et al., 2014 ; Sacharowski et al., 2015 ; Jégu et al., 2017 ), two ACTIN-RELATED PROTEINS (ARP4 and ARP7) ( Kandasamy et al., 2003 ), and a single Leaf and Flower Related (LFR) protein ( Wang et al., 2009 ; Lin et al., 2021 ). In addition, two homologous BRM‐interacting proteins (BRIP1 and BRIP2) ( Yu et al., 2020 ), three bromodomain‐containing proteins (BRD1, BRD2, and BRD13) ( Jarończyk et al., 2021 ; Yu et al., 2021 ), ANGUSTIFOLIA3 ( Vercruyssen et al., 2014 ), and two TRIPLE PHD FINGERS proteins (TPF1 and TFP2) ( Diego-Martin et al., 2022 ) have been identified as components of the SWI/SNF CRC.…”
Section: Introductionmentioning
confidence: 99%
“…The LFR gene is essential for leaf and flower development in Arabidopsis ( Wang et al., 2012 ; Lin et al., 2018 ; Lin et al., 2021 ). LFR encodes an Armadillo (ARM)-repeat domain-containing protein that is predicted to be a subunit of the SWI/SNF CRC ( Wang et al., 2009 ; Lin et al., 2021 ; Diego-Martin et al., 2022 ; Shang and He, 2022 ). In this study, we found that the disruption of LFR led to reduced freezing tolerance in Arabidopsis.…”
Section: Introductionmentioning
confidence: 99%